Hazard Identification Risk Assessment and Risk Control Measures in Micro, Small, and Medium Enterprises Cuanki in Kasemen District, Serang City - Siti Darifah; Agus Sugiharto; Amalia Fitri Hakim; Hanifah Rahmawati; Aulia Prima Purbasari; Dhiaullzzah Ramnadhani; Rifdha Haifa Salsabila; Hani Halimatusadiah; Indira Monique; Fariz Ath Thaariq Shalih; Najimah Zhahirotun Huwaida (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Micro, Small, and Medium Enterprises (MSMEs) Cuanki Bakti Mulia is a company engaged in the food industry that produces cuanki in Indonesia. It is at high risk due to the severity and possibility of accidents causing severe injuries. This study aims to identify hazards, assess risks, and control at MSMEs Cuanki Bakti Mulia, Kasemen District, Serang City. The method used is Hazard Identification Risk Assessment and Control (HIRAC). The object of study is the work of MSMEs Cuanki Bakti Mulia, namely all potentially hazardous activities. Data from the company, interviews, direct surveys of production equipment, and machines in the production process were collected for this study. The results of the study showed that many risks were identified. The process of making and rolling meatball dough, and fried dumpling dough had a high risk rating compared to others. In dough making, ingredients in flour that come into direct touch with the breath might irritate the nasal and mouth mucosa and create respiratory problems. In dough rolling, hands are exposed to vibration for a long time, and noise causes hearing loss. Several protection and prevention measures have been taken, mainly to protect workers from workplace accidents and maintain the hygiene of the food produced. The proposed hazard controls are replacing firewood with gas stoves when frying to make tofu and fried dumplings, setting restrictions on workers' working hours, and ensuring adequate rest by reducing working hours. The company needs to provide and equip with Personal Protective Equipment (PPE).